A Critical Analysis of the Information Technology Act, 2000 vis-à-vis Mitigation of Child Pornography - Deb, Aishwarya; Chowdhury, Prithwish Roy (Christ University Law Journal, 2018)
This paper investigates the efficacy of the provisions of the Information Technology Act, 2000 dealing with child pornography which has been, more often than not, considered to be a victimless crime. The author argues that the ambiguity in the provisions of the Act has led to arbitrariness in investigations and procedures dealing with the offence of child pornography. This paper, by critically analysing the provisions of the aforementioned legislation vis-à-vis child pornography, attempts to show that the menace can be mitigated by following a victim-centred approach and also by incorporating certain procedural standards, as per the Budapest Convention, 2001. The authors also make an attempt to propose certain changes which are required in the existing legislation, in order to effectively deal with the said crime i